Determination of the protective effects of Hua‐Zhuo‐Jie‐Du in chronic atrophic gastritis by regulating intestinal microbiota and metabolites: combination of liquid chromatograph mass spectrometer metabolic profiling and 16S rRNA gene sequencing - Pingping Zhou; Xinyu Hao; Yu Liu; Zeqi Yang; Miaochan Xu; Shaowei Liu; Shixiong Zhang; Tianxiao Yang; Xiaomei Wang; Yangang Wang (BMC, 2021)
Abstract Background Hua-Zhuo-Jie-Du (HZJD), a Chinese herbal prescription consisting of 11 herbs, is commonly used in China to treat chronic atrophic gastritis (CAG). We aimed to determine the effect of HZJD on the microbiome-associated metabolic changes in CAG rats. Methods The CAG rat models were induced by 1-methyl-3-nitro-1-nitrosoguanidine (MNNG) combined with irregular fasting and 2% sodium salicylate, which was intragastrically administrated in fasted animals for 24 weeks. The CAG rats in the Chinese medicine (CM) group were administered a daily dose of 14.81 g/kg/day HZJD, and the vitacoenzyme (V) group were administered a daily dose of 0.08 g/kg/day vitacoenzyme. All animals were treated for 10 consecutive weeks, consecutively. Hematoxylin and eosin (H&E) staining was used to assess the histopathological changes in the gastric tissues. An integrated approach based on liquid chromatograph mass spectrometer (LC-MS) metabolic profiling combined with 16S rRNA gene sequencing was carried out to assess the effects of HZJD on CAG rats. Spearman analysis was used to calculate the correlation coefficient between the different intestinal microbiota and the metabolites. Results The H&E results indicated that HZJD could improve the pathological condition of CAG rats. The LC-MS results indicated that HZJD could significantly improve 21 gastric mucosal tissue perturbed metabolites in CAG rats; the affected metabolites were found to be involved in multiple metabolic pathways, such as the central carbon metabolism in cancer. The results of 16S rRNA gene sequencing indicated that HZJD could regulate the diversity, microbial composition, and abundance of the intestinal microbiota of CAG rats. Following HZJD treatment, the relative abundance of Turicibacter was increased, and the relative abundance of Desulfococcus and Escherichia were decreased in the CM group when compared with the M group. Spearman analysis revealed that perturbed intestinal microbes had a strong correlation with differential metabolites, Escherichia exhibited a negative correlation with l-Leucine, Turicibacter was negatively correlated with urea, and Desulfococcus exhibited a positive correlation with trimethylamine, and a negative correlation with choline. Conclusions HZJD could protect CAG by regulating intestinal microbiota and its metabolites.